Upaya Meningkatkan Kinerja Guru PAI dalam Menyusun RPP Berbasis Kecakapan Abad 21, Literasi dan HOTS melalui Workshop di SMP se-Depok Kabupaten Sleman - Ida Uswatun Hasanah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
The weakness of teachers in drafting the RPP based on 21st century, literacy and HOTS in particular, is still widely seen in the mismatch between basic competency (KD) and the formulation of indicators referring to 21st century learning, literacy and HOTS, not yet appropriate between the material and learning methods used, inconsistency between learning activities with selected methods and models. This is what causes the teacher not to maximally implement planning well in the learning process in the classroom. This research aims to improve the performance of PAI teachers in drafting RPP based on 21st century, literacy and HOTS through workshop activities in junior high school in Depok District, Sleman, 2019/2020. This research uses the method of research actions performed in three cycles. The results showed that workshop activities can improve the teacher's performance in achieving a well-formulated standard. The teacher's performance in drafting the RRP of 62.5% in cycle I increased to 73.75% in cycle II, and increased to 86.25% in the III cycle. The results of this surveillance action show that the implementation of workshops can improve teacher performance.